Energy Savings in 5G-Advanced Radio Access Networks: Downlink Signaling Adaptation - Vatanian, Nazanin; Oliveira da Costa, Gustavo Wagner; Roth-Mandutz, Elke; George, Geordie; Franchi, Norman (2024 IEEE 100th Vehicular Technology Conference (VTC2024-Fall), 2024)
As energy consumption of cellular networks continues to rise, its impact on the environment and operating costs have become a pressing concern. With the goal of improving energy efficiency by reducing the energy consumption, Network Energy Savings (NES) is considered by 3GPP as one of the key enhancements of the 5G-Advanced and 6G standardization. This paper addresses a key time-domain NES technique being standardized by 3GPP, namely, adaptation of downlink common signals, providing a comprehensive evaluation based on system level simulations. We propose a novel approach to dynamically adapt the periodicity of downlink common signals based on network demand. The results demonstrate great benefits of the dynamic adaptation of downlink common signals in terms of energy saving gain
Keywords: network energy savings; NES; energy efficiency; power saving; 5G NR; common signals adaptation; 5G-Advanced; 6G